Effect of Nanodiamonds on the Optoelectronic Properties of TiO2 Photoanode in Dye-Sensitized Solar Cell - Ahmad, Muhammad Shakeel; Pandey, Adarsh Kumar; Rahim, Nasrudin Abd (Springer, 2018)
Low charge transfer resistance and high light absorption ability of TiO2-based photoanodes are the crucial challenges in the field of dye-sensitized solar cells (DSSCs). In this study, nanodiamonds (NDs) have been introduced in TiO2 matrix to investigate their effect on the performance of DSSCs. Colloidal suspension method has been employed for the synthesis of TiO2/NDs nanocomposites. Various concentrations of NDs, i.e., TiO2–0.2 wt%NDs, TiO2–0.5 wt%NDs, TiO2–1 wt%NDs, TiO2–3 wt%NDs and TiO2–5 wt%NDs, have been trialed for the fabrication of nanocomposite photoanode using doctor blade method with D719 dye as sensitizer. Scanning electron microscopy and X-ray diffraction methods were used to study the morphology, composition and dispersion of NDs in TiO2 matrix. UV–visible absorption spectroscopy, photocurrent–voltage characteristics and electrochemical impedance spectroscopic measurements were conducted to characterize the performance of DSSCs. The results show that the photoconversion efficiency is highly dependent on the concentration of NDs in the photoanode due to high light absorption, dye loading and heterojunction symmetry of the system. A solar cell based on a photoanode containing 3 wt% NDs showed a power conversion efficiency of 0.47% compared to 0.26% efficiency of unmodified photoanode.